Agreement options for negotiation on material location decision of housing development. Issue 2 (17th January 2020) - Utomo, Christiono; Rahmawati, Yani
Abstract : Purpose: Different housing development stakeholders need to cooperate and collaborate to perform various project activities. Housing development requires infrastructure development, which includes preparation of sand material embankment as much as ± 200, 000 m 3 . The objectives are to find a model for agreement options and coalition, to validate the algorithms of the best fit for material locations and to determine how much the proposed agreement option was achieved. This study provides a structured methodology that can lead to systematic support system and automated negotiation for decision-making on housing development process. Design/methodology/approach: Agreement option on group decision techniques was applied to determine the relative value of the alternative solutions for performing the function of project solutions. Analytical hierarchy process based on satisficing option was applied for decision process and game theory-based agent system for coalition formation. It is conducted in two stages that determine the decision preference and decision process consisting of four steps. The steps are constructing decision hierarchy, making judgment and synthesis, determining payoff optimum and analyzing the best fit option for all decision-makers. Findings: The proposed model enables each decision-maker to select individually its coalition. It will improve the value of strategic decision. All solutions are chosen by more than one decision-maker and coalitions, where all decision-makers agree with the result. It becomes possible location for the material of a housing development. A support model enables negotiation process in group decision. Decision algorithms are based on the cooperative game theory to develop the agreement options and coalition formation. Similar research studies were carried out in this area, but this research is – to the knowledge of the authors – the first to apply the satisficing of value-based on desirable and considerable. Research limitations/implications: The result is limited to the first-round negotiation of collaborative decision. A trade-off algorithm among decision-maker preference is needed for negotiation process. Future research is to continue working on multi-attribute decision-making, specifically on the process of eliciting user preference models such as neural network application and value function, and on establishing expert quantitative data from qualitative description of the feature of the alternative solution. It will need the development of trade-off algorithms to analyze value of technical solution in real time. Practical implications: The support model can be extended to an automated negotiation and in different strategic decision on all stages of housing development. Social implications: The satisficing algorithm of the coalition will satisfy all stakeholders. This will reduce any potential conflict. Originality/value: Combination of value-based decision, group decision and collaborative support. Application of coalition formation for agreement options is used to select the best fit material location. It is based on satisficing game theory rather than optimization.